A view from the vendor's side: factors that determine satisfaction. (2nd October 2017) - Gopalakrishnan, Shanthi; Guilbault, Melodi; Ojha, Abhoy K.
Abstract : Purpose: With the growth in outsourcing it is imperative to understand the vendor's satisfaction with IT outsourcing relationships since contractual and relationship factors affect the ability of vendors and clients to work together over time. A recent study demonstrated that relational factors such as trust and information exchange dominated in their ability to explain client satisfaction when compared to contractual factors. The purpose of this paper is to further examine how the relational factors work together to lead to vendor satisfaction in an outsourcing relationship. Design/methodology/approach: A survey was developed and pre-tested with vendors in India and client firms in the USA that used international IT vendors. Using data collected from 214 vendor firms in the Indian subcontinent the paper examines the main effect of two client focused variables, namely, competence-based trust and client dependence on vendor satisfaction; it also explores whether social control moderate the main effect relationships. Findings: The findings indicate that client dependence and competence-based trust were significant direct predictors of vendor satisfaction. Social control or the ability to resolve conflicts positively moderated the effect client dependence on vendor satisfaction. But it did not impact the effect of competence-based trust on vendor satisfaction. Research limitations/implications: The authors identify three limitations: a dyadic analysis using both the client and the vendor perspective would have provided a richer understanding of the relationship; since the data were collected on a cross-sectional basis, it is hard to make predictive assessments; and a limited response rate. Practical implications: These findings help us understand the factors that impact vendor satisfaction in an outsourcing relationship and this is one of the keys to maintaining a long-term relationship between transacting parties. Originality/value: Previous studies have explored the relational aspects of a vendor-client interaction from the client's point of view and, here, the authors take the vendor's perspective, which is increasingly important due to the increasing complexity of work outsourced. Besides exploring the direct effect competence-based trust and client dependence on vendor satisfaction, the authors also analyze the role of social control as a moderator.